Re-thinking HIV-Related Stigma in Health Care Settings: A Qualitative Study - Gagnon, Marilou (Journal of the Association of Nurses in AIDS Care, 2015)
People living with HIV (PLWH) continue to endure stigma and discrimination in the context of health care. This paper presents the findings of a qualitative study designed to (a) describe stigmatizing and discriminatory practices in health care settings, and (b) explore both symbolic and structural stigma from the perspectives of PLWH. For the purpose of this qualitative study, 21 semi-structured in-depth interviews were conducted in the province of Quebec, Canada. The data were analyzed following the principles of thematic analysis. During analysis, three themes were identified, and relations between these themes were delineated to reflect the experiences of participants. The findings suggest that HIV-related stigma in health care settings is episodic in nature. The findings also suggest that HIV-related stigma is experienced through interactions with health care providers (symbolic stigma) and, finally, that it is applied systematically to manage risk in the context of health care (structural stigma).
Keywords: 2000 à aujourd'hui; amérique du nord; amériques; approches et analyses; canada; corps; cours; discipline; inégalités; justice sociale; premier cycle; périodes historiques; québec; régions géographiques; santé; sciences humaines; systèmes d'oppressions; thématiques; travail social; trs1205

CIRFF 2015 - Soirée d'ouverture et plenière d'ouverture avec Natasha Kanapé Fontaine (2015)
7e Congrès international des recherches féministes dans la francophonie (CIRFF2015) Plénière d’ouverture sous le thème Penser Créer Agir avec : - Natasha Kanapé Fontaine, poète et slameuse. Lundi 24 août, salle Marie-Gérin-Lajoie, UQAM.
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; antiféminisme; antiracisme; approches et analyses; environnement; féminisme autochtone; histoire et politique; identités; identités culturelles; justice sociale; maternité; mohawk; poésie; périodes historiques; québec; ressource en ligne; régions géographiques; terre nouricière; territoire; thématiques; écriture des femmes*

Le droit criminel, la justice transformatrice et la violence faites aux femmes : regards croisés - Chagnon, Rachel; Côté, Liliane; Mickaelian, Virginie (Ligue des Droits et Libertés, 2015)
Keywords: 1900-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; amérique du nord; amériques; approches et analyses; canada; changement social; discipline; droit; droit criminel; histoire et politique; justice réparatrice; justice sociale; périodes historiques; québec; ressource en ligne; régions géographiques; science politique et droit; sofia; thématiques; violences; violences conjugales; violences sexuelles

Real queer?: sexual orientation and gender identity refugees in the Canadian refugee apparatus - Murray, David A. B. (Rowman & Littlefield International, Ltd., 2015)
An ethnographic exploration of sexual orientation and gender identity (SOGI) refugee claimants' experiences of navigating the complex discourses, protocols, practices and personnel of Canada's refugee determination system. "How do I prove I'm gay?" This is the central question for many refugee claimants who are claiming asylum on the basis of sexual orientation persecution. But what are the inherent challenges in obtaining this proof? How is the system that assesses this predicated upon homonormative frameworks and nervous borders? What is the impact of gender, race and class? What is an `authentic' sexual or gender identity and how can it be performed? Real Queer? is an ethnographic examination of the Canadian refugee apparatus analysing the social, cultural, political and affective dimensions of a legal and bureaucratic process predicated on separating the `authentic' from the `bogus' LGBT refugee. Through interviews, conversations and participant observation with various participants ranging from refugee claimants to their lawyers, Refugee Protection Division staff and local support group workers, it reveals the ways in which sexuality simultaneously disrupts and is folded into the nation-state's dynamic modes of gate-keeping, citizenship and identity-making, and the uneven effects of these discourses and practices on this category of transnational migrants
Keywords: 2000 à aujourd'hui; LGBTQIA2+; amériques; approches et analyses; canada; capitalisme; cours; histoire et politique; intersectionnalité; justice sociale; migration; migrations queer; premier cycle; périodes historiques; queer; régions géographiques; sex2283; système colonial; systèmes d'oppressions; thématiques

Nānīawig Māmawe Nīnawind. Debout et solidaires. Femmes autochtones disparues ou assassinées au Québec - Québec, Femmes autochtones au; Bergeron, Annie; Boileau, Alana; Lévesque, Carole (Femmes autotchtones au Québec, 2015)
Le présent document fait état des résultats d’une enquête exploratoire effectuée par Femmes Autochtones au Québec (FAQ) en ce qui a trait à la situation des femmes autochtones disparues ou assassinées au Québec. Cette enquête a bénéficié du soutien financier du ministère de la Justice du Québec et du Réseau de recherche et de connaissances relatives aux peuples autochtones (DIALOG). Elle visait principalement à consigner et à mettre en valeur la parole des Autochtones de différents horizons et provenances, de même que celles des membres des familles de femmes autochtones disparues ou assassinées, principales personnes concernées par la problématique.
Keywords: amériques; anthropologie; approches et analyses; canada; cours; discipline; droits des femmes*; droits des femmes* autochtones; féminisme autochtone; histoire et politique; justice sociale; pol4105; premier cycle; québec; racisme; régions géographiques; science politique et droit; sciences humaines; sexisme; système colonial; systèmes d'oppressions; thématiques; violences

Nous voyez-vous? : pratiques sociales médiatisées sur le web de deux groupes de femmes haïtiennes pour contrer les violences post-séisme envers les femmes : la visibilité comme stratégie pour la justice sociale - Roussel, Mélissa (Université du Québec à Montréal, 2015)
Que sait-on des problèmes sociaux qui sont apparus ou amplifiés suite au séisme de 2010 en Haïti, et particulièrement concernant les violences faites aux femmes? La contribution de cette recherche est de décrire des pratiques sociales médiatisées des groupes de femmes Kay Fanm et SOFA dans l'espace public qu'est le web, dans le but de contrer l'injustice sociale (Fraser, 2004) que sont les violences faites aux femmes en contexte post-séisme en Haïti, à des fins de transformations sociales. L'analyse d'une cartographie des outils web répertoriés et des textes qui y sont diffusés met en évidence que les groupes à l'étude utilisent des outils du web 1.0 et 2.0 pour rendre visible un discours (à des fins de reconnaissance) et que les ressources communicationnelles doivent être disponibles et accessibles (à des fins de redistribution) pour tous. En somme, ce mémoire de recherche de maîtrise souligne la pertinence de s'intéresser aux pratiques médiatisées sur le web pour contrer des injustices sociales si des acteurs souhaitent développer et améliorer leurs pratiques. ______________________________________________________________________________ MOTS-CLÉS DE L’AUTEUR : Analyse du discours, cartographie web, pratiques sociales, médiatisation, actes de langages, violences faites aux femmes, post-séisme.
Keywords: IREF; amériques; approches et analyses; discipline; haïti; justice sociale; militance; médias sociaux; mémoires/thèses; ressource en ligne; régions géographiques; sciences humaines; thématiques; travail social; violences